If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = ln(ln(8x)) Remove parenthesis around (8x) y = ln(ln * 8x) Reorder the terms for easier multiplication: y = ln(8ln * x) Multiply ln * x y = ln(8lnx) Remove parenthesis around (8lnx) y = ln * 8lnx Reorder the terms for easier multiplication: y = 8ln * lnx Multiply ln * lnx y = 8l2n2x Solving y = 8l2n2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 8l2n2x
| 9x+1=7x+14 | | 0.02(y-6)+0.12y=0.06y-0.7 | | 7x+x-5=7x+2 | | -18+x=x+144 | | x=7-8y | | 7c-3c+10=2c+20 | | 72x+y=3 | | (8+x)(4x-1)= | | x^2-14x=-81 | | 18x+6y=3 | | sin^2x-1= | | 6x+6=-7+2x+21 | | h(t)=16t^2+140t | | 41n(x+5)=8 | | 11+6=-4x-9x | | x+26+4x=-18-4x-24 | | 5y-3=3y-5 | | 7r-3= | | y=(x+9y)(x^3-9) | | x*x-5x=4 | | 2(x+6)=x+22 | | 1.5(x+6)-0.5(x-24)=16 | | 2ln(2-x)+1=2 | | -16x^2+72x+3=0 | | -2w^5(-6w^3)= | | 1/5x-7/5=-5x+4/3 | | -3(5x-2)+9x=-42 | | 4(z+1)=16 | | -2x-y=0 | | -2(8-y)=-6y | | 6.57x=3.48x | | 7w-9=13-4w |